NOTE ON THE ANALYSIS OF SIZE FREQUENCIES OF SETIPINNA TATY (VALENCIENNES) OF THE LOWER SUNDERBANS REGION (HOOGHLY-MATLAH ESTUARY) - Datta, D K; Datta, P (Indian Journal of Fisheries, 2011)
Large scale fishing takes place around Frazerganj in the Hooghly-Matlah estuary with the ht;lp of bagnets (Pillay and Ghosh, 1962), locally known as ’binjal’ or ’behundi jal’, during the winter season. A substantial portion of the catch obtained consists of Setipinna spp. mostly S. taiy. During 1969-’70 and 1970-’71 the catches of Setipinna species were 249 tonnes and 420 tonnes forming 14.05% and 14.09% of the total landings during the season and 51.33% and 52.25% respectively of the total annual catch of the species from the entire Hooghly-Matlah estuary. The length frequencies of 5. taty, from these catches would give a good indication of the age-structure of the total catch from the estuary, besides gian idea of the age-structure of the seasonal population of the species in the particular area.